ROLE OF BARIUM MEAL EXAMINATION IN DIAGNOSIS OF PEPTIC ULCER - Nawaz, Muhammad; Jehanzaib, Muhammad; Khan, Khalid; Zari, Mohammad (Journal of Ayub Medical College Abbottabad, 2008)
Background: Peptic ulcer is a sore in the protective lining (mucosal lining) of the gastrointestinal tract and develops when the lining is damaged. The objectives of this Descriptive Validational study were to determine the validity of Barium Meal examination in the diagnosis of peptic ulcer disease in comparison to the gold standard, i.e., endoscopic evaluation in peptic ulcer disease. The study was conducted at Radiology Department Khyber Teaching Hospital Peshawar from November 2000 to March 2004. Methods: A total of 115 patients with signs and symptoms of peptic ulcer disease were selected for this study and were subjected for this diagnostic modality. The diagnosis of benign/malignant peptic ulcer was made by barium meal examinations. In all these patients the diagnosis was later on confirmed by endoscopy and or surgery. Results: Of the 115 patients, 80 were male and 35 were female patients. Their ages ranged from 27-75 years with mean age of 49 years. Fifty two patients had duodenal ulcer, 30 patients gastric ulcer, and 33 patients had normal radiological findings. In 6 out of 30 patients with gastric ulcer had radiological evidence of malignant gastric ulcer. Conclusion: Efficiency of Barium meal examination in diagnosis of peptic ulcer is good and most of peptic ulcers can be diagnosed by this method. Keyword: Barium meal, Peptic ulcer, Endoscopy.